The Evaluation and the Accreditation Process of Greek HEIs with an Emphasis on Primary Education Departments - Gregory T. Papanikos (Athens Institute for Education and Research, 2023)
This paper examines the quality evaluations of the Greek Universities highlighting those which offer a full-fledged study program of primary education. There are eight principles-criteria according to which each university is evaluated. For each principle, scores may range from 1 (noncompliance with the principle) to 4 (fully compliance). I present and compare results of the Greek university evaluations completed by the Hellenic Quality Assurance and Accreditation Agency (HQA). Surprisingly, no university has been graded as non-compliant in any of the eight principles-criteria. These evaluations are performed by an alleged "external" and "independent" committee. For all practical purposes, they are, nevertheless, based on subjective and biased opinions of academics affiliated with international universities with links to Greece and its universities. Independent and evidence-based evaluations paint a different picture. Universities which get perfect scores in the quality evaluation processes perform badly in the pertinent international ranking systems. As a case study, their primary education departments have lower research performance with high variability between faculty members and departments. Given that one criterion of evaluating quality is research, then not all Greek universities can be evaluated as highly performing research institutions, either in absolute or relevant terms. This criterion of quality is not satisfied by the primary education departments of Greek universities. According to this evidence, using the HQA as an agency to assess and accredit quality is useless. It should be abolished. A new system should be based on objective criteria such as independent teaching evaluations and research performance. These do not require any committee to evaluate performance and can be constructed on evidence-based policy. The latter relies solely on rigorously established objective facts.